The piloting and evaluation of the graduate employability skills app - Jimoyiannis, Athanassios; Boyle, Elizabeth; Scott, Graham G.; Petersen, Sobah Abbas; Topolewska-Siedzik, Ewa; Tsiotakis, Panagiotis; Abbas, Aisha; Baxter, Gavin; Iqbal, Maria (Frontiers in Computer Science, 2025)
The Graduate Employability Skills app (GES-APP) is an innovative application that aims to assist students in higher education in thinking about and reflecting on their employability skills. This paper describes the iterative, 3 phase evaluation framework that was used in designing and evaluating the app and presents the key findings at each stage of the process. The iterative evaluation approach ensured that the GES-APP was modified at each phase by taking account of staff and students’ suggestions for improvements. Participants in the evaluation were students and staff from the 4 partner institutions of the EU-funded GES-APP project. The initial piloting focused on self-reporting of employability skills and participants provided positive comments about this activity, the key idea, content organization and functionality. They considered that it was innovative, meaningful and important and motivated them in exploring their employability skills and attitudes. Participants also provided many useful suggestions that were used to improve the layout and the quality of graphics, enhance users’ interactivity and feedback, and clarify the role of the employability coach. This revised prototype of the GES-APP was used in the quantitative and qualitative piloting of the extended app in phase 2. Further improvements were made and tested in phase 3. This involved a more rigorous, quasi-experimental design testing the final version of the GES-APP, using pre-and post-questionnaires to record students’ understanding of their employability skills, employer needs and career preparation. Statistically significant changes were found following the GES-APP intervention along two key dimensions: (a) Understanding employer needs and the labor market and (b) preparing for a career. This evaluation suggests that students would welcome digital support of this kind in helping them make the transition from higher education into the world of work.